HUBUNGAN ANTARA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA SISWA DI SMA PGRI 2 PALEMBANG - Deka Ratih Afrika; Neta Dian Lestari; Riswan Aradea (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
The research objective was to determine the closeness of the relationship between Craft and Entrepreneurship Subjects (PKWU) and Entrepreneurial Interest in class XI students of SMA PGRI 2 Palembang. Research problems, namely; Is there a relationship between Craft and Entrepreneurship Subjects with Entrepreneurship Interest in Class XI Students at SMA PGRI 2 Palembang? The research method is a quantitative method with the type of correlation research. Data collection techniques in this study were documentation and questionnaires with Likert scale guidelines. The results showed that the average score of students in the subject of Craftsmanship and Entrepreneurship (X) was 84.75 in the "Good" category and the average results of the questionnaire on entrepreneurship interest (Y) was 84.86% in the "Very Interested" category. Hypothesis test results obtained t count (7,199) > t table (1,666) and the significance test there is a significant relationship between the subject of Craft and Entrepreneurship with the interest in entrepreneurship students at SMA PGRI 2 Palembang by 39% and the remaining 61% is influenced by other factors.Keywords: Craft and Entrepreneurship Subject and Entrepreneurial Interests